siRNA machinery in whitefly (Bemisia tabaci). - Santosh Kumar Upadhyay (PLoS ONE, 2013)
BACKGROUND: RNA interference has been emerged as an utmost tool for the control of sap sucking insect pests. Systemic response is necessary to control them in field condition. Whitefly is observed to be more prone to siRNA in recent studies, however the siRNA machinery and mechanism is not well established. METHODOLOGY/PRINCIPAL FINDINGS: To identify the core siRNA machinery, we curated transcriptome data of whitefly from NCBI database. Partial mRNA sequences encoding Dicer2, R2D2, Argonaute2 and Sid1 were identified by tblastn search of homologous sequences from Aphis glycines and Tribolium castaneum. Complete encoding sequences were obtained by RACE, protein sequences derived by Expasy translate tool and confirmed by blastp analysis. Conserved domain search and Prosite-Scan showed similar domain architecture as reported in homologs from related insects. We found helicase, PAZ, RNaseIIIa, RNaseIIIb and double-stranded RNA-binding fold (DSRBF) in Dicer2; DsRBD in R2D2; and PAZ and PIWI domains in Argonaute2. Eleven transmembrane domains were detected in Sid1. Sequence homology and phylogenetic analysis revealed that RNAi machinery of whitefly is close to Aphids. Real-time PCR analysis showed similar expression of these genes in different developmental stages as reported in A. glycines and T. castaneum. Further, the expression level of above genes was quite similar to the housekeeping gene actin. CONCLUSIONS/SIGNIFICANCE: Availability of core siRNA machinery including the Sid1 and their universal expression in reasonable quantity indicated significant response of whitefly towards siRNA. Present report opens the way for controlling whitefly, one of the most destructive crop insect pest.